Escape Chaotic Dimension using Iterated Function System that are not Based on Code Space Method - Mohammed, Arkan J (Al-Nahrain Journal of Science, 2018)
In this paper some IFS attractors are defined using the Escape Time Algorithm applied to certain dynamical system. This algorithm is used to compare how fast different points in the window W escape to the region V under the action of a dynamical system. The chaotic behavior of these attractors have been shown in a new way not based on code space method and a new approach for computing fractal dimension of these chaotic attractors are given which we called escape chaotic dimension. Two algorithms are proposed to find the attractors based on Escape Time Algorithm, and to find its fractal dimensions, they are carried out using Delphi Programming language.